Body Dissatisfaction dan Keterkaitannya dengan Subjective Well-Being pada Perempuan Masa Emerging Adulthood - Kurnia, Yemima Carolina; Lestari, Sumi (Mediapsi, 2020)
In this research, we aimed to examine the relationship between body dissatisfaction and three aspects of subjective well-being, which included life satisfaction, positive affect, and negative affect. Drawing from accidental sampling, participants were 306 women between the ages of 18 and 25 years who were in the period of emerging adulthood and domiciled in Malang, East Java. Designed as a correlational survey, results in this research revealed that high levels of body dissatisfaction corresponded with low levels of life satisfaction and positive affect. Conversely, high levels of body dissatisfaction corresponded with high levels of negative affect. We explain the theoretical implications of these empirical findings in the discussion section, which also highlights the limitations of the present work as well as recommendations for follow-up studies to overcome these limitations. Penelitian ini bertujuan untuk mengetahui hubungan antara body dissatisfaction dan tiga aspek subjective well-being, yang mencakup kepuasan hidup, afek positif, dan afek negatif. Subjek penelitian adalah 306 perempuan berusia 18-25 tahun yang berada pada masa emerging adulthood dan berdomisili di Kota Malang, Jawa Timur, yang direkrut atas dasar accidental sampling. Studi korelasional dalam penelitian ini menunjukkan bahwa tingginya body dissatisfaction berkaitan dengan rendahnya kepuasaan hidup dan afek positif. Sebaliknya, tingginya body dissatisfaction berkaitan dengan tingginya afek negatif. Implikasi teoritis dari temuan-temuan empiris ini dielaborasi di bagian diskusi, yang juga membahas kelemahan-kelemahan dalam penelitian ini serta rekomendasi studi lanjutan untuk menutupi kelemahan-kelamahan tersebut.Â